The Interjection !Olé!— origins in Caló (Andalusian Para-romani). - Sayers, William (Romance Notes, 2023)
The Spanish exclamation olé is traced to Caló and is one result of the interaction of the paradigms of demonstrative pronouns, personal pronouns, and locative adverbs, when Common Romani was confronted with Andalusian Spanish. Not a compliment or hortatory exclamation directed at the flamenco performer or bullfighter, it was initially an ostensive deictic comment addressed to other members of the public and meant "(look at/listen to) that person (artist) over yonder" and thus promoted community pride and cohesion.